A study of some of the causes of trade dispute in Malaysia / Radzli Jaafar - Jaafar, Radzli (Faculty of Law, 1982)
In approaching this study, Chapter 1 deals with, firstly, an introduction whereby the respective roles of the tripartite system is noted. Chapter 2 is a study of the definition of what is a trade dispute with certain commentaries being made where appropriate, al though it may not be exhaustively so. Chapter 3 deals with the nature of trade disputes which arise mainly f'rom matters connected with the employment or non-employment, terms of employment and condition of work. It is important to note that some of the causes are mentioned and discussed:; where appropriate and proper to do so. Chapter 4 is on the general causes of trade disputes. Apart from the already mentioned causes touched upon in the nature of trade disputes, an overall study is made by stating and commenting on the roles, sttitudes and problems of the three sectors, namely, the employer, workmen and .the government. A general study of' the other causes such as communication problems, non-d.isclosure of information, want of consultation and expansion of trade tmion activities are discusset. The causes of trade disputes are viewed from the social, economic, legal and management aspects. Finally the effects of trade disputes are briefly dealt with. Chapter 5 deals with the proposals towards better indus trial harmony. Al though not entirely innovative but its application may help minimise the causes of trade disputes. The proposals basically deals wi th the changing of' attitudes towards work, working towards efficiency and its rewards and better management style 0 The study of this paper is concluded by summarising the causes of trade disputes.